Concepts in mature T-cell lymphomas – highlights from an international joint symposium on T-cell immunology and oncology*. Issue 4 (3rd April 2017) - Herling, Marco; Rengstl, Benjamin; Scholtysik, René; Hartmann, Sylvia; Küppers, Ralf; Hansmann, Martin-Leo; Diebner, Hans H.; Roeder, Ingo; Abken, Hinrich; Newrzela, Sebastian; Kirberg, Jörg
Abstract: Growing attention in mature T-cell lymphomas/leukemias (MTCL) is committed to more accurate and meaningful classifications, improved pathogenetic concepts and expanded therapeutic options. This requires considerations of the immunologic concepts of T-cell homeostasis and the specifics of T-cell receptor (TCR) affinities and signaling. Scientists from various disciplines established the CONTROL-T research unit and in an international conference on MTCL they brought together experts from T-cell immunity, oncology, immunotherapy and systems biology. We report here meeting highlights on the covered topics of diagnostic pitfalls, implications by the new WHO classification, insights from discovered genomic lesions as well as TCR-centric concepts of cellular dynamics in host defense, auto-immunity and tumorigenic clonal escape, including predictions to be derived from in vivo imaging and mathematical modeling. Presentations on novel treatment approaches were supplemented by strategies of optimizing T-cell immunotherapies. Work packages, that in joint efforts would advance the field of MTCL more efficiently, are identified.